2020
DOI: 10.3892/etm.2020.8440
|View full text |Cite
|
Sign up to set email alerts
|

Propofol protects human cardiac cells against chemical hypoxiainduced injury by regulating the JNK signaling pathways

Abstract: Propofol is a widely used intravenous anesthetic shown to exert a cardioprotective role against oxidative stress and ischemia/reperfusion injury in rat cardiac H9c2 cells. However, the regulatory mechanisms and functions of propofol in human cardiomyocytes remain unknown. The present study chemically induced hypoxia with cobalt chloride (CoCl 2 ) to mimic cardiomyocyte ischemic injury in human cardiac AC16 and HCM cells. To investigate its underlying mechanisms, propofol was added to the cells before the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In the current study, we focused on the effect and mechanism of propofol on mitochondrial malfunction and dynamic imbalance, which were induced by hypoxia in hippocampal neurons. In consistence with previous publications carried out in cardiac cells [ 52 ], hepatic cells [ 53 ], and microglia [ 54 ], we proved propofol may protect hypoxia-induced mitochondrial malfunction and dynamic imbalance through its antioxidant property in hippocampal neurons ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we focused on the effect and mechanism of propofol on mitochondrial malfunction and dynamic imbalance, which were induced by hypoxia in hippocampal neurons. In consistence with previous publications carried out in cardiac cells [ 52 ], hepatic cells [ 53 ], and microglia [ 54 ], we proved propofol may protect hypoxia-induced mitochondrial malfunction and dynamic imbalance through its antioxidant property in hippocampal neurons ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 89%
“…46 Studies have shown that stimulating JNK and p38-MAPK has a proapoptotic effect, whereas activating ERK has an anti-apoptotic effect following the activation of the MAPK signaling cascade, which is closely associated with cellular apoptosis, autophagy, inflammation and oxidative stress. [47][48][49] The MAPK signaling pathway may play a significant role in the occurrence and development of AD. A positive association has been found between the disease and increased levels of p-p38MAPK and p-JNK in the blood of AD patients.…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
“…In summary, this study demonstrated that propofol influences both levels of oxidative stress and inflammation [ 62 ]. The antioxidative properties of propofol were also observed in human cardiac cells, and the protective effect was attributed to an activation of the JNK signaling pathway [ 64 ].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%